Cognitive Activation in a Close-Up View: Triggers of High Cognitive Activity in Students During Group Work Phases - Groß-Mlynek, Lena; Graf, Tanja; Harring, Marius; Gabriel-Busse, Katrin; Feldhoff, Tobias (Frontiers in Education, 2022)
Cognitive student activation describes the mental stimulation of learners to engage in a deeper mental investigation of the subject matter within the learning context. Based on the "Angebots-Nutzungs-Modell” (Supply-Use Model), a lesson that is cognitively activating can be understood as a learning opportunity provided by the teacher, which learners can make use of based on their individual ability. This paper focuses on the side of the users, i.e. the cognitive activity of students during phases of collaborative work. Based on a videotaped English lesson of a 10th-grade class (N = 18), low- and medium-inference, indicator-based coding and rating systems were used to investigate the micro level of student-teacher and student-student interactions. The focus of the analysis was to examine triggers of student’s individual high cognitive activity during group work phases. After a basic coding to achieve a precise description of students activities, the level of cognitive activity in selected sequences was coded by a medium-inference rating system. Subsequently the sequences in which a student’s cognitive activity had previously been rated as high were assessed in a content analysis (Mayring 2015) to determine what triggered a particular phase of high cognitive activity. Analyses show that the students are cognitively engaged at varying degrees and at different times. It is interesting to note that high cognitive activity is not necessarily interrelated with the frequency of verbal participation. Even students with little verbal participation several times exhibit high cognitive engagement. This can be attributed to different aspects and triggers: On the one hand, students are cognitively activated by working with the material and by stimuli provided by the teacher. On the other hand, they engage in cognitive activity among themselves by asking one another questions or by benefiting from the discussion between other group members.